IBM z/OS V2R2 availability management - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the Availability Management areas with IBM z/OS® V2R2. This book is one of a series of IBM Redbooks that take a modular approach to providing information about the updates that are included with z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful and we welcome your feedback.
Number on resource description page: SG24829000. - Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed January 22, 2016)
Keywords: z/OS; Database management; Information storage and retrieval systems -- Management; Bases de données; Gestion; Information storage and retrieval systems; Management